Case report: Evaluation of myocardial microcirculation in patients with breast cancer after anthracycline chemotherapy by using intravoxel incoherent motion imaging - Li, Shilan; Tian, Di; Li, Xin; Li, Jia; Song, Qingwei; Xia, Yunlong; Li, Zhiyong (Frontiers in Cardiovascular Medicine, 2022)
Introduction Anthracycline chemotherapy drugs can produce cardiotoxicity in patients with breast cancer, leading to myocardial cell death and fibrosis, further developing into cardiac failure. However, the condition of myocardial microcirculation was unknown in breast cancer after anthracycline chemotherapy. As a result, intravoxel incoherent motion (IVIM) imaging was used to non-invasively observe the condition of myocardial microcirculation in a patient with breast cancer after anthracycline chemotherapy. Case report A 43-year-old female patient with a right breast lump was reported. Preoperative ultrasound-guided needle biopsy showed invasive carcinoma of the right breast with fibroadenoma. Sentinel lymph node biopsy combined with simplified radical surgery for right breast cancer was performed. Postoperative pathological findings reported breast cancer (pT2N2M0 IIIA). The patient underwent eight sessions of the EC-TH chemotherapy scheme, and the EC and the TH schemes were adopted for the first four sessions and the last four sessions, respectively. During chemotherapy, during which there was the occurrence of Grade II myelosuppression, chest CT and abdomen CT showed no metastasis, and ECG and cardiac ultrasound reports returned to normal. Cardiac cine magnetic resonance and IVIM imaging were performed at the beginning of the first chemotherapy session (baseline) and after the third, fifth, and eighth chemotherapy sessions, respectively. We found that the fast apparent diffusion coefficient (ADCfast) and f parameters appeared to show a downward trend from the baseline to the fifth chemotherapy session, where the IVIMfast values declined from 163 × 10−3 mm2/s to 148 × 10−3 mm2/s and finally to 134 × 10−3 mm2/s and f values declined from 45% to 36% and then to 30%, respectively. ADCfast and f values showed an inclination from the fifth and eighth chemotherapy sessions. Conclusion Our case report showed that IVIM technology can likely detect non-invasive myocardial microcirculation early and quantitatively after anthracycline chemotherapy in patients with breast cancer. That is, IVIM technology seems to be helpful for cardiovascular risk monitoring and prognosis assessment of myocardial microcirculation in patients with breast cancer after anthracycline chemotherapy.